Penyuluhan Pemakaian BTP (Bahan Tambahan Pangan) pada Masyarakat di Desa Pagaruyung, Kecamatan Tapung, Kabupaten Kampar - Johan, Vonny Setiaries; Pato, Usman; Efendi, Raswen; Fitriani, Shanti; Zalfiatri, Yelmira; Ibrahim, Ahmad; Hamzah, Faizah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Food additives are compounds that are deliberately added to food in certain quantities and sizes and are involved in processing, packaging and/or storage. Food additives are mixed ingredients that are not part of the food raw materials, but are added to food to influence the nature or shape of the food, including colorings, preservatives, flavorings, anti-caking agents, whiteners and thickeners. Most people use food additives without clear measurements, which will have negative consequences for people's health. Therefore, outreach activities are needed to the public regarding the proper and correct use of food additives. The aim of this service activity is to provide information about food additives to the community, especially the community in Pagaruyung village, Tapung District, Kampar Regency. With these service activities and publications, it will help disseminate information regarding the correct use of food additives. Before public outreach, a pre-test was given, where the level of public understanding regarding BTP was 60%. After presenting the BTP material, a post test was carried out where public understanding increased to 92%. For evaluation of the implementation of community service activities, almost all people felt the benefits and were very satisfied with the activities carried out.